MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI DENGAN MEDIA GAMBAR PADA SISWA SEKOLAH DASAR - Nur Azizah, Fidya; Candra Dewi; Amalya Trisuci Dewanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve descriptive text writing skills using image media for elementary school students at SDN 03 Madiun Lor. This research was conducted using a collaborative classroom action research (PTK) method, consisting of two learning cycles. This research involved 29 fifth grade students at SDN 03 Madiun Lor as research subjects. The data analysis techniques used in this research include quantitative and qualitative analysis through tests and observations carried out before and after the learning cycle. Based on the research results, it can be concluded that in the pre-cycle, 10 students succeeded in achieving completion, while 19 other students did not complete. In the first cycle, there was an increase with 15 students achieving completion and 14 students still not completing it. In the second cycle, the number of students who achieved completion increased to 25 students, while only 4 students had not yet completed it. These results indicate that the level of mastery in writing skills began to increase after the application of image media since the pre-cycle.